2014
DOI: 10.1016/j.celrep.2014.08.058
|View full text |Cite
|
Sign up to set email alerts
|

Circulating AIM Prevents Hepatocellular Carcinoma through Complement Activation

Abstract: Hepatocellular carcinoma (HCC) is a widespread fatal disease and the third most common cause of cancer deaths. Here, we show the potent anti-HCC effect of the circulating protein AIM. As in adipocytes, AIM is incorporated into normal hepatocytes, where it interferes with lipid storage. In contrast, AIM accumulates on the HCC cell surface and activates the complement cascade via inactivating multiple regulators of complement activation. This response provokes necrotic cell death specifically in AIM-bound HCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
106
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 61 publications
5
106
1
Order By: Relevance
“…From these results, it is likely that carcinogenesis was induced in hepatocytes at a considerably high rate only by the HFrD. This fact became apparent because we used AIM -/-mice, in which cancerous hepatocytes are not eliminated and keep growing (Maehara et al 2014).…”
Section: Hcc Development In Aimmentioning
confidence: 95%
See 4 more Smart Citations
“…From these results, it is likely that carcinogenesis was induced in hepatocytes at a considerably high rate only by the HFrD. This fact became apparent because we used AIM -/-mice, in which cancerous hepatocytes are not eliminated and keep growing (Maehara et al 2014).…”
Section: Hcc Development In Aimmentioning
confidence: 95%
“…No wild-type mice showed such multiple HCC tumors after the same HFrD challenge ( Fig. 2A,B), similar to those fed the HFD (Maehara et al 2014), consistent with the findings of previous reports by other groups who showed that HCC is rarely induced in wild-type mice by HFrD or HFD challenge alone (Hill-Baskin et al 2009;Kumamoto et al 2013;Yoshimoto et al 2013). RNA sequencing analysis of the liver from AIM -/-mice fed the HFrD at 0, 12 and 52 weeks showed changes in the expression of genes for cancer-related canonical pathways in parallel with HCC development (Fig.…”
Section: Hcc Development In Aimmentioning
confidence: 98%
See 3 more Smart Citations